The non-syndromic familial thoracic aortic aneurysms and dissections maps to 15q21 locus - Chandok Gurangad; Farahani Maryam M; Sadeghpour Anita; Keramati Ali R; Mani Arya (BMC, 2010)
Abstract Background Thoracic aortic aneurysms and dissections (TAAD) is a critical condition that often goes undiagnosed with fatal consequences. While majority of the cases are sporadic, more than 20% are inherited as a single gene disorder. The most common familial TAA is Marfan syndrome (MFS), which is primarily caused by mutations in fibrillin-1 (FBN1) gene. Patients with FBN1 mutations are at higher risk for dissection compared to other patients with similar size aneurysms. Methods Fifteen family members were genotyped using Affymetrix-10K genechips. A genome-wide association study was carried out using an autosomal dominant model of inheritance with incomplete penetrance. Mutation screening of all exons and exon-intron boundaries of FBN1 gene which reside near the peak Lod score was carried out by direct sequencing. Results The index case presented with agonizing substernal pain and was found to have TAAD by transthoracic echocardiogram. The family history was significant for 3 first degree relatives with TAA. Nine additional family members were diagnosed with TAA by echocardiography examinations. The affected individuals had no syndromic features. A genome-wide analysis of linkage mapped the disease gene to a single locus on chromosome 15q21 with a peak Lod score of 3.6 at fibrillin-1 (FBN1) gene locus (odds ratio > 4000:1 in favour of linkage), strongly suggesting that FBN1 is the causative gene. No mutation was identified within the exons and exon-intron boundaries of FBN1 gene that segregated with the disease. Haplotype analysis identified additional mutation carriers who had previously unknown status due to borderline dilation of the ascending aorta. Conclusions A familial non-syndromic TAAD is strongly associated with the FBN1 gene locus and has a malignant disease course often seen in MFS patients. This finding indicates the importance of obtaining detailed family history and echocardiographic screening of extended relatives of patients with non-syndromic TAAD to improve the outcome. In addition, association of non-syndromic TAAD with the Marfan disease gene locus poses the question whether secondary prevention strategies employed for Marfan syndrome patients should be applied to all patients with familial TAAD.